A new genus and species of sand-hopper, Mauritiorchestia fayetta gen. nov., sp. nov. (Amphipoda, Talitridae) from Mauritius - Green, M.a.a.; Appadoo, C.; Lowry, J.k.; Myers, A.a. (Zootaxa, 2021)
A new genus and species, Mauritiorchestia fayetta gen. nov., sp. nov., of talitrid amphipod is described from beaches in Mauritius. Mauritiorchestia differs significantly from the closely related genus Platorchestia in the maxilla 1 palp (absent in Mauritiorchestia, vestigial in Platorchestia) and in the dactylus of gnathopod 1 (simplidactylate in Mauritiorchestia, cuspidactylate in Platorchestia).